Investigation of the Prevalence and Clinical Characteristics of Early Complication of Electrode Dislodgement in Patients has Indications for Permanent Pacemaker Implantation - Giang S. Tran; Si D. Chu (Wolters Kluwer Medknow Publications, 2024)
Objective: To investigate the prevalence and reopen the drive procedure of early complications of electrode dislodgement in patients with an indication for permanent pacemaker implantation at the Vietnam National Heart Institute. Methods: This is a study on patients who received permanent pacemaker implantation at the Vietnam National Heart Institute during the period from August 1, 2019 to March 30, 2020. Results: In all cases with complications of electrode dislodgement after implantation indicated to reopen the machine to handle complications, the results of handling complications are safe and stable. Conclusion: There is a positive relationship between the events of electrode dislodgement on the pacemaker and the degree of tricuspid valve regurgitation with a statistically significant difference (P < 0.01, OR = 8.2; 95% CI: 1.6-42.9).